Anti-inflammatory Elafin in human fetal membranes - Stalberg, Cecilia; Noda, Nathalia [UNESP]; Polettini, Jossimara [UNESP]; Jacobsson, Bo; Menon, Ramkumar (De Gruyter, 2017)
Elafin is a low molecular weight protein with antileukoproteinase, anti-inflammatory, antibacterial and immunomodulating properties. The profile of Elafin in fetal membranes is not well characterized. This study determined the changes in Elafin expression and concentration in human fetal membrane from patients with preterm prelabor rupture of membranes (PPROM) and in vitro in response to intra-amniotic polymicrobial pathogens. Elafin messenger RNA (mRNA) expressions were studied in fetal membranes from PPROM, normal term as well as in normal term not in labor membranes in an organ explant system treated (24 h) with lipopolysaccharide (LPS), using quantitative reverse transcription-polymerase chain reaction (RT-PCR). Enzyme-linked immunosorbent assay (ELISA) measured Elafin concentrations in culture supernatants from tissues treated with LPS and polybacterial combinations of heat-inactivated Mycoplasma hominis (MH), Ureaplasma urealyticum (UU) and Gardnerella vaginalis (GV). Elafin mRNA expression in fetal membranes from women with PPROM was significantly higher compared to women who delivered at term after normal pregnancy (5.09±3.50 vs. 11.71±2.21; P<0.05). In vitro, LPS-stimulated membranes showed a significantly increased Elafin m-RNA expression (P<0.05). However, the protein levels after LPS stimulation was not changed. Similarly, polymicrobial-treated fetal membranes also showed no changes in Elafin protein concentrations compared to untreated controls. Higher Elafin expression in PPROM fetal membranes suggests a host response to an inflammatory pathology. However, lack of Elafin response to LPS and polymicrobial treatment is indicative of the minimal anti-inflammatory impact of this molecule in fetal membranes.
Keywords: Amnion; bacteria; chorion; inflammation; pathway; PI3; polymicrobial infection; PPROM; preterm birth; risk